Two Decades of Advertisement Engagement : A Bibliometric and Network Analysis - Ubgade, Pritha Nasery; Joshi, Sujata (Indian Journal of Marketing, 2024)
Purpose : One of the most popular research subjects in the past few years has been the effect of advertising on consumers. An advertisement’s persuasiveness is determined by its ability to engage consumers, which is the underlying concept. Despite a wide variety of theoretical and empirical literature available in the field of advertisement engagement, mapping the knowledge structure of advertisement engagement literature remains relatively less undertaken. Methodology : The goal of this study was to map the literature on advertisement engagement by performing a bibliometric and network analysis in light of this gap. In order to map the body of knowledge on advertisement engagement, this study examined significant journals, yearly publications, ground-breaking writers, and significant papers published between 2000 and 2024. Findings : The findings of the study suggested that the USA is the most contributing country, and the International Journal for Advertising published a maximum number of studies in the field of advertising engagement. Furthermore, Yang et al.’s (2021) research made the most contribution to the field of advertisement engagement on social media platforms of all researchers. Practical Implications : The study mapped how participation in advertisements affected the surrounding environment. Originality Value : It has been discovered that more research is being done in the area of advertising engagement due to the growing popularity of more recent media. This study provides a framework for future research on advertisement engagement while mapping the literature and trends in the field.